“EFECTO DE LA INVERSIÓN EXTRANJERA DIRECTA Y LA URBANIZACIÓN EN LA CONTAMINACIÓN AMBIENTAL. UN ESTUDIO PARA PAÍSES DE AMÉRICA DEL SUR, PERÍODO 1990-2018.” - Guamán Malla, Angélica del Cisne (2021)
Foreign direct investment (FDI) is an essential element for the growth of the economies of the host countries by facilitating greater employment opportunities and diffusion of technology. However, the installation of foreign companies and the urbanization whose process persists in South America imply greater pressure on the use of natural resources, compromising the quality of the environment. Therefore, the research work focuses on examining the effect of foreign direct investment and urbanization on environmental pollution in South America, period 1990-2018. For this, a GLS model and the Granger causality test were estimated, using industrialization and human capital as control variables. The results show that FDI and urbanization positively influence environmental pollution in South American countries. In addition, the presence of a bidirectional causal relationship between these variables was identified. According to the results, it is suggested that those responsible for formulating policies focus on orienting or diversifying FDI towards strategic sectors that support a sustainable economy or production. In addition, it is necessary for the environment to establish greater control in foreign companies through considerable sanctions. Finally, policies are suggested aimed at regulating and controlling the expansion of the urban perimeter and the promotion of sustainable urban means of transport.